Pre-andean tectonic events from albian to eocene in the middle Magdalena valley and situation of the western flank of the proto-eastern cordillera (Colombia) (2018)
For years in Colombia research has been mainly centered on the knowledge of the most recent uplifting of the Eastern Cordillera, and on the evaluation of the Tertiary units in many basins to understand the recent deformation. Recently, due to the necessities of the oil industry to evaluate new targets, new information has been acquired on Cretaceous units form the Eastern Cordillera and Middle Magdalena Valley. The aim of this work is to analyse the data which gives evidence of deformation in the basin of Middle Magdalena Valley during the Cretaceous. The Cretaceous units are exposed in the Eastern Cordillera, but not in the Middle Magdalena Valley, where only a few outcrops are known. Instead a lot of seismic information is available on this area and some wells that have drilled the Cretaceous units. Using large seismic reflection sections and well information, I could identify important events, unconformities, and faults which were inverted in different stages during the Lower Cretaceous to the Eocene, prior to the Andean Orogeny. For that, I will show some key seismic sections interpreted in the Middle Magdalena Valley (MMV). This interpretation will be validated with sections using surface field information and well information, and the structural styles will be discussed. My results highlight the new proposed interpretation for the cretaceous sequence, showing more details especially in the MMV, due to the seismic coverage and well information, and in the Western Eastern Cordillera (WEC) with more difficulty using some surface information that was collected during this work as well as preexisting information from available literature, how there were multiple phases of deformation that include different states of uprising or relative sea level change during the Cretaceous period, which is important to understand the real process that affected the Cretaceous behavior and also to suggest that tectonics and sea level changes or their interaction could be more complex during this time. Based on the construction and analysis of transgressive-regressive curves and Fischer relative accommodation space plots, I interpreted system tracts and sea-level variations and recognized major surface boundaries surface (unconformities or their correlative conformities) at the Barremian-Aptian, during the Late Albian-Early Cenomanianand and Early Campanian times. Aditionally, based on tracts interpreted and surface boundaries, I built regional paleo-facies maps from Berriasian to Coniacian-Santonian, showing several periods of regression and transgression till early Campanian. From seismic interpretation made in this work, using seismic stratigraphy and wheeler diagrams, five sequences (S) and five unconformities (SU) were identified as sequence boundaries: recognized at the Jurassic-Cretaceous, Late Barremian-Early Aptian (~125 Ma), and at the Albian-Cenomanian (~100 Ma), Santonian-Campanian (~ 80 Ma), and Paleocene-Eocene boundaries, these unconformities or their correlative conformities (SU) have a regional extension. The thermochronological information collected, prepared, analyzed, interpreted and modeled in this work, helped me to recognized two events of heating and two events of cooling for samples deposited before 85 Ma. The heating events occurred from the sedimentation of the units till ~85– 80 Ma and from ~70 Ma to ~10 Ma and the cooling events occurred between ~80 Ma till ~70 Ma and from ~10-2 Ma. The paleo-geothermal gradient versus the present-day thermal gradient make it possible to identify the presence of unconformities. The integration of the structural reconstructions made in this work through the Cretaceous, considering the sequences (S) and the discordances (SU) and the transgressive-regressive sequences (paleo-facies maps), shows the relation between deformation, deposition and erosion and when each of these events happened during the Cretaceous in these basins (MMV and WEC). My tectonic and geodynamic reconstruction makes it possible to conclude that from the Jurassic to the Paleocene, repetitive tectonic extension and compression events produced by a cyclic subduction regime, explain the relative sea fluctuation and the deposition, exhumation and erosion phases observed in the MMV and WEC during the Cretaceous. Finally, the presence of accreted blocks (for ex. Quebradagrande) is undeniable. However, the deformation of the upper plate in my model is not dependent on these accreted terranes, but rather on the subduction regime, for example changes in the plate subduction angle (steep or flat subduction), the convergence rate, the polarity of subduction, the age of the slab, etc.